Distribution Transformer Control Optimization Simulation Using PID Controller : Adaptive Algorithm Based Approach to Improve System Stability - Nurqalbi (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
Effective control of distribution transformers is crucial to ensuring stability and efficiency in electrical distribution systems. This study presents a simulation-based optimization of distribution transformer control using a PID (Proportional-Integral-Derivative) controller, enhanced by an adaptive algorithm to improve system performance and stability. The study evaluates transient response across three key parameters—voltage, current, and temperature—by comparing system performance with and without proportional control. Key metrics such as overshoot, peak time, rise time, and settling time are analyzed to assess the impact of PID control on system stability. The simulation results demonstrate that implementing a PID controller with a Kp value of 2.0 can reduce overshoot by 52.34% for current, voltage, and temperature compared to a system without proportional control. The system's peak time significantly decreases from 10 seconds without Kp to 0.30 seconds with Kp = 2.0, while the rise time is reduced from 4.65 seconds to 0.20 seconds. However, the settling time remains constant at around 10 seconds. An adaptive algorithm-based approach is proposed to further enhance control performance by dynamically adjusting the Kp value in response to changing system conditions. These findings indicate that an optimized PID controller can improve the stability of distribution transformer systems, providing faster and more accurate responses while reducing the risk of instability due to load fluctuations.